Pelatihan dan Pendampingan Penggunaan Media Pembelajaran Berbasis Multimedia pada Guru Sejarah SMA Negeri 4 Ambon - Touwe, Sem; Pattiasina, Johan; Ima, Wa (Universitas Pattimura, 2024)
The integration of multimedia-based learning media in education is increasingly important to improve the effectiveness of learning. Research shows that multimedia can improve students' interest and learning outcomes in history subjects. However, challenges in adopting multimedia include lack of teacher training. Training and professional development are needed to ensure the effective use of multimedia in the education curriculum. Despite significant benefits, research that focuses on the implementation of multimedia in history teaching is still limited. This activity aims to improve teacher skills in developing multimedia learning media that meet the requirements for history learning in secondary schools in Indonesia. The media learning mentoring activity at SMA Negeri 4 Ambon City involved teachers with instructors from FKIP Unpatti. The training methods included lectures, demonstrations, and exercises for the development of effective learning media. The stages included lectures on media theory, demonstrations of media development steps, and practical exercises by participants. Evaluation was carried out to ensure the quality of the media produced. The PKM activity at SMA Negeri 4 Ambon City successfully provided a basis for developing learning media. Despite limited time, teachers were able to create interactive media. The evaluation results showed significant benefits of multimedia in improving learning. This collaboration emphasizes the importance of higher education and schools to improve the quality of education. Continuous support and training will strengthen the contribution of teachers.